2021
DOI: 10.1177/08927057211048534
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of dissimilar joining between metal and polymer hybrid structure with different joining processes

Abstract: In this century, innovation and technology are required to fabricate the hybrid joint of metal and polymers. Due to their lightweight and anti-corrosion properties, the mixed components are increasingly used to produce lightweight hybrid structures such as aerospace and automobiles. It is essential to develop welding techniques for joining dissimilar materials and instead use them in engineering structures. The bonding mechanism of the weld joint has varied depending upon the welding process. In the present re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 193 publications
0
5
0
Order By: Relevance
“…1,3,4 Furthermore, MPCs are one of the most useful systems in bio separation, 5 magnetic resonance imaging, 6 cancer treatment, 7 drug delivery, 8 and antimalarial activity. 9 The hybrid structures of polymers and metals can be found in the vehicle industry as anti-knocking components 10,11 and also as photocatalysts in the treatment of organic dyes in wastewater. 12−19 The literature has reported the incorporation of various polymers, including porphyrin, pyridinyl, pyrene, polyethyleneimine, salecan, pullulan, and chitosan, into MPC struc-tures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…1,3,4 Furthermore, MPCs are one of the most useful systems in bio separation, 5 magnetic resonance imaging, 6 cancer treatment, 7 drug delivery, 8 and antimalarial activity. 9 The hybrid structures of polymers and metals can be found in the vehicle industry as anti-knocking components 10,11 and also as photocatalysts in the treatment of organic dyes in wastewater. 12−19 The literature has reported the incorporation of various polymers, including porphyrin, pyridinyl, pyrene, polyethyleneimine, salecan, pullulan, and chitosan, into MPC struc-tures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Due to its lightweight and corrosion-resistant properties, it is essential to develop welding techniques to join dissimilar materials and use them in engineered structures. 17 In terms of composite hybrid connections, experiments and finite element analysis models are often used for investigation. Kelly et al 18 carried out experiments on hybrid joints, which showed that adhesive-bolt hybrid joints have higher strength and stiffness, and better fatigue life.…”
Section: Introductionmentioning
confidence: 99%
“…Thermal joining is also referred to as direct thermal joining because these processes lack additional components. Different energy sources like ultrasound [2], induction [3] and lasers [4] can be used. Lasers have the advantage of non-contact heat input and a high degree of automatization.…”
Section: Introductionmentioning
confidence: 99%